1982
DOI: 10.1128/mcb.2.11.1339
|View full text |Cite
|
Sign up to set email alerts
|

Mouse cells contain two distinct ras gene mRNA species that can be translated into a p21 onc protein.

Abstract: The Kirsten (Ki) and Harvey (Ha) strains of murine sarcoma virus encode a 21,000-dalton protein (p21 ras) which is the product of the transforming gene of these viruses. Normal cells express low levels of p21 ras encoded by cellular genes (Ki-ras and Ha-ras) homologous to the Ki and Ha murine sarcoma virus transformation genes. A bone marrow-derived mouse cell line, 416B, has been shown to express unusually high levels of p21 ras. In this manuscript, we investigated the molecular biology of p21 ras gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
1

Year Published

1984
1984
1997
1997

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 27 publications
3
29
1
Order By: Relevance
“…We compared the amount of c-/rasK and c-i-risH transcripts in polysomal poly(A)' RNA obtained from livers of normal and sham-operated rats and from regenerating livers at 12,18,24,36,48. and 96 h after partial hepatectomy by using the dot-blot procedure.…”
Section: Resultsmentioning
confidence: 99%
“…We compared the amount of c-/rasK and c-i-risH transcripts in polysomal poly(A)' RNA obtained from livers of normal and sham-operated rats and from regenerating livers at 12,18,24,36,48. and 96 h after partial hepatectomy by using the dot-blot procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Our studies of the same cells ( SW480, Calu-1, SK-N-SH, T24, peripheral blood lymphocytes) are broadly in agreement (DJW et al, unpublished data). Subsequent reports have used a restricted range of probes which would not distinguish the K-ras isoforms: HiHi 3 (Campisi et al, 1984;Ellis et al, 1981;Lockett and Sleigh, 1987;Sejersen et al, 1985), HiHi 380 (Ellis et al, 1981(Ellis et al, , 1982Goyette et al, 1984;Yaswen et al, 1985) and pY413 (George et al, 1985;Leon et al, 1987). Where PCR has been used, primers were chosen within exons 1 and 3 (Pal et al, 1993).…”
Section: Differential Expression Of K-ras Isoforms S Pells Et Almentioning
confidence: 99%
“…Where PCR has been used, primers were chosen within exons 1 and 3 (Pal et al, 1993). Two transcripts of the K-ras gene are translated into functional p21 K-ras (Ellis et al, 1982) but di er in the 3' untranslated region and poly(A) tail George et al, 1985;McGrath et al, 1983). The failure to note size heterogeneity even though both contain exon 4A and 4B sequences George et al, 1985) is probably due to inadequate resolution and low expression of the KrasA isoform.…”
Section: Differential Expression Of K-ras Isoforms S Pells Et Almentioning
confidence: 99%
“…5). In the cell extract made from the KC cells we in normal cells, and in some cases specific enhancement of expression has been detected in specialized cells or at precise stages of embryonic development (4,9 (1,6,23). In many cases, independent data have indicated that these homologs are expressed as mRNAs and proteins in many normal cells (8,10,26,27 with 0.007 ml of monoclonal antibody for 2 h at 4°C, followed by incubation with 0.060 ml of protein A-Sepharose coated with rabbit anti-rat immunoglobulin G for 1 h at 4°C.…”
mentioning
confidence: 99%